Perceived Difficulties in Physical Tasks and Physical Fitness in Treatment- and Non-Treatment-Seeking Youths with Obesity - Giada Ballarin; Maria Rosaria Licenziati; Olivia Di Vincenzo; Luca Scalfi; Giuliana Valerio (MDPI AG, 2022)
Youths with obesity are more likely to experience physical and psychosocial distress which strongly limits physical activity, with consequences on the quality of life. Most evidence of lower physical fitness and physical activity levels has been reported in treatment-seeking samples, while few data are available in community samples. Our aim was to assess whether perceived difficulties in physical tasks and physical fitness performance differed between treatment- and non-treatment-seeking youths with obesity, enrolled from a hospital (H) and a school (S). Three hundred fifty-one youths (269 from H and 82 from S) were enrolled. Sports participation, sedentary habits and perceived difficulties in physical tasks were assessed by interview. Six-minute walk test (SMWD) and long jump (LJ) were performed. BMI Z-score, sedentary time and perceived difficulties were higher in H vs. S. In addition, youths from H scored worse in SMWD and LJ. For the same BMI Z-score, the perceived difficulties and physical fitness were poorer in the H compared to the S group. The setting (H) was the stronger predictor of perceived difficulties and lower performance. Our findings underline that physical aspects imposed by obesity are more evident in treatment-seeking youths. Counseling related to perceived difficulties in physical tasks and performance is useful to treat youth with obesity with appropriate and personalized modalities.